PRODUCTION AND APPLICATION OF MOUSE ANTISERUM TO HUMAN ESTROGEN RECEPTORS - Zhang, Lei; Sun, Sulian; He, Luowen (Chinese Journal of Cancer Research, 2013)
A polyclonal antibody to peptide containing 15 amino acids and corresponding to region- D of hmmm estrogen receptors (hERo) was obtained in mice by immunization with the coupler of peptide and KLH. Using this antisermm, the ER status of paraff'm - embeded sections of 95 hlmmn breast carcinomas were studied. The corrcs~nding rate for determination of ER status between inmamohistochemical staining (IHC) and dextran coated charcoal (DCC) assay was 89.5%. The concordance for semiquantitative grades was 69.3%. In addition, in situ hybridization (ISH) of 15 frozen sections of same sample using digoxigenin labeled dlYrP to identify the expression of ER mRNA for confirming the 1HC also be used. This technique revealed more specific, sensitive and convenient than DCC. The results of ISH were fully consistent with HIC (100 %). Above results show that the mouse antisermn to hEl~ obtained in this study is specific and sensitive for IHC assay of ER and ]HC is a valuable adjtmct and/or alternative to the biochemical method for determination of the ER status of breast cancer.